Question 16 (OR 1 st question)
If y = x ^{ sin β‘x } + sinβ‘ (x ^{ x } ), find dy/dx
Get live Maths 1-on-1 Classs - Class 6 to 12
CBSE Class 12 Sample Paper for 2019 Boards
Question 1 Important
Question 2
Question 3
Question 4 (Or 1st) Important
Question 4 (Or 2nd)
Question 5
Question 6
Question 7 Important
Question 8 (Or 1st) Important
Question 8 (Or 2nd)
Question 9
Question 10 (Or 1st) Important
Question 10 (Or 2nd)
Question 11 Important
Question 12 (Or 1st)
Question 12 (Or 2nd)
Question 13 (Or 1st) Important
Question 13 (Or 2nd)
Question 14 Important
Question 15
Question 16 (Or 1st) You are here
Question 16 (Or 2nd) Important
Question 17
Question 18
Question 19 Important
Question 20 Important
Question 21 (Or 1st)
Question 21 (Or 2nd) Important
Question 22
Question 23 Important
Question 24 (Or 1st)
Question 24 (Or 2nd) Important
Question 25
Question 26 (Or 1st) Important
Question 26 (Or 2nd)
Question 27 (Or 1st) Important
Question 27 (Or 2nd) Important
Question 28
Question 29 Important
CBSE Class 12 Sample Paper for 2019 Boards
Last updated at March 16, 2023 by Teachoo
Question 16 (OR 1 st question)
If y = x ^{ sin β‘x } + sinβ‘ (x ^{ x } ), find dy/dx
Get live Maths 1-on-1 Classs - Class 6 to 12
Question 16 (OR 1st question) If y = π₯^sinβ‘π₯ +sinβ‘γ(π₯^π₯)γ, find ππ¦/ππ₯ Let u = π₯^sinβ‘π₯ , π£=sinβ‘γ(π₯^π₯)γ Thus, y = u + v Differentiating π€.π.π‘.π₯ ππ¦/ππ₯ = ππ’/ππ₯ + ππ£/ππ₯ Calculating derivative of u and v separately Solving π π/π π u = π₯^sinβ‘π₯ Taking log both sides logβ‘π’ = log π₯^sinβ‘π₯ logβ‘π’ = sinβ‘π₯ . log π₯ Differentiating π€.π.π‘.π₯ (π(logβ‘γπ’)γ)/ππ₯ = π/ππ₯ (sinβ‘γπ₯ logβ‘π₯ γ ) By product Rule (uv)β = uβv + vβu where u = sin x & v = log x (π(logβ‘γπ’)γ)/ππ₯ = (π(sinβ‘π₯))/ππ₯.log π₯+sin π₯ . (π(logβ‘π₯))/ππ₯ (π(logβ‘γπ’)γ)/ππ’ Γ ππ’/ππ₯ = cosβ‘π₯ logβ‘π₯ + sinβ‘π₯ 1/π₯ 1/π’ " Γ " ππ’/ππ₯ = cos π₯β‘logβ‘π₯ + sinβ‘π₯ 1/π₯ ππ’/ππ₯ = π’ (γcos xγβ‘γlogβ‘γπ₯+ 1/π₯γ sinβ‘π₯ γ ) Putting back π’ = π₯^π ππβ‘π₯ ππ’/ππ₯ = π₯^π ππβ‘π₯ (cosβ‘γlogβ‘γπ₯+ 1/π₯γ sinβ‘π₯ γ ) Solving π π/π π v = sinβ‘γ(π₯^π₯)γ Let t = π₯^π₯ Taking log both sides logβ‘π‘ = log π₯^π₯ logβ‘π‘ = π₯ log π₯ Differentiating π€.π.π‘.π₯ (π(logβ‘γπ‘)γ)/ππ₯ = π/ππ₯ (π₯ logβ‘π₯ ) (π(logβ‘γπ‘)γ)/ππ₯ = (π(π₯))/ππ₯.log π₯+π₯ . (π(logβ‘π₯))/ππ₯ (π(logβ‘γπ‘)γ)/ππ₯ = (π(π₯))/ππ₯.log π₯+π₯ . (π(logβ‘π₯))/ππ₯ (π(logβ‘γπ‘)γ)/ππ‘ Γ ππ‘/ππ₯ = 1.log π₯+π₯Γ1/π₯ 1/t Γ ππ‘/ππ₯ = log π₯+1 ππ‘/ππ₯ = t(log π₯+1) Putting t = xx ππ‘/ππ₯ = π₯^π₯ (πππ π₯+1) Now, v = sinβ‘γ(π₯^π₯)γ v = sinβ‘γ(π‘)γ Differentiating w.r.t. x ππ£/ππ₯ = (π(sinβ‘π‘))/ππ₯ ππ£/ππ₯ = (π(sinβ‘π‘))/ππ‘ Γ ππ‘/ππ₯ ππ£/ππ₯ = cos t Γ ππ‘/ππ₯ ππ£/ππ₯ = cosβ‘γ(π₯^π₯)γ (πππ π₯+1)π₯^π₯ Now, from (1) ππ¦/ππ₯ = ππ’/ππ₯ + ππ£/ππ₯ ππ¦/ππ₯ = π₯^π ππβ‘π₯ (cosβ‘γlogβ‘γπ₯+ 1/π₯γ sinβ‘π₯ γ )+ cosβ‘γγ(π₯γ^π₯)γ (πππ π₯+1)π₯^π₯